2009
DOI: 10.1007/s00468-009-0372-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevation-dependent climate sensitivity in Eucalyptus pauciflora Sieb. ex Spreng

Abstract: We examine climate sensitivity in tree-ring chronologies from Eucalyptus pauciflora Sieb. ex Spreng at three elevations-1,350, 1,475 and 1,600 m above the sea level. Consistent with the principle that the sensitivity of tree-ring chronologies increases with proximity to the limits of tree growth, statistics reflecting chronology reliability increased with elevation. Climatological analyses of the three elevation classes revealed that whilst ring width is significantly and positively correlated with maximum air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…7). Negative correlations between tree growth and previous growing season temperatures have been reported for other species in the south-eastern and southern TP (Liang and Wang et al 2010;Lv and Zhang 2012) as well as other areas (Yu et al 2006;Brookhouse and Bi 2009;Fang et al 2010;Lo et al 2010). It is possible that high temperatures in summer will intensify evapotranspiration and thus reduce available moisture content and consequently reduce radial growth (Lara et al 2001;Savva et al 2006;Fang et al 2010).…”
Section: Radial Growth and Climatementioning
confidence: 99%
See 1 more Smart Citation
“…7). Negative correlations between tree growth and previous growing season temperatures have been reported for other species in the south-eastern and southern TP (Liang and Wang et al 2010;Lv and Zhang 2012) as well as other areas (Yu et al 2006;Brookhouse and Bi 2009;Fang et al 2010;Lo et al 2010). It is possible that high temperatures in summer will intensify evapotranspiration and thus reduce available moisture content and consequently reduce radial growth (Lara et al 2001;Savva et al 2006;Fang et al 2010).…”
Section: Radial Growth and Climatementioning
confidence: 99%
“…Daniels and Veblen 2004;Dang et al 2009b;Elliott and Kipfmueller 2011). Previous studies in many mountainous areas have reported that climate-growth relationships might vary along altitudinal gradients (Splechtna et al 2000;Takahashi et al 2003;Yu et al 2006;Dang et al 2007;Massaccesi et al 2008;Peng et al 2008;Brookhouse and Bi 2009) and the importance of limiting factors may vary in shaping forest regeneration with altitude (Duan et al 2009). Tree recruitment in high-altitude areas, such as tree-line ecotones, is mainly controlled by climate (Szeicz and Macdonald 1995;Camarero and Gutiérrez 2004;Wang et al 2006;Dang et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Based on dendroclimatological studies of trees at different elevations, it is generally considered that precipitation is the main limiting factor of tree growth at the lower forest limit, whereas the radial growth of trees at the upper forest limit is constrained principally by temperature [63][64][65][66]. However, some studies have claimed that this does not hold for some extremely arid or humid areas in which the main climatic limiting factors might not change with elevation [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…When there are good results for both the statistical analysis of the calibration and validation phases of a proxy record a dendrochronological climate reconstruction can be deemed representative of past climate conditions. Brookhouse and Bi, 2009;(Eucalyptus pauciflora) Allen et al, 2013Buckley et al, 1997;Cook et al, 1991;1996;2000;Drew et al, 2013 (Lagarostrobos franklinii) Allen, 2002;Allen et al, 2001; Figure 1 shows the location of these studies. Buckley et al, 1997;Cook et al 1991;1996;2000;Ogden, 1978b, B = Allen et al, 2001, Buckley et al, 1997Pearman et al, 1976, C = Allen, 2002, Allen et al, 2011Ogden, 1978a;1978b, D = Allen et al, 2001, E = Allen et al, 2001, F = Brookhouse and Brack, 20062008, G = Brookhouse et al, 2008McDougal et al, 2012, H = Brookhouse andBi, 2009;Heinrick and Banks, 2005, I = Cullen and Grierson, 2007, J = Cullen and Grierson, 2009Sgherza et al, 2010, K = Baker et al, 2008Drew et al, 2011;Mucha, 1979, L = Ash, 1983a1983b;Boysen et al, 2014;Heinrich and Banks, 2006a;Heinrich et al, 2008;…”
Section: Dendroclimatologymentioning
confidence: 99%
“…To help determine the full climatic conditions of the area ringwidth was compared to snow depth in the preceding winter and spring and a strong negative correlation was observed for all months with snow on the ground. A follow-up study using E. pauciflora from the Brindabella Range, along the western boarder of the Australian Capital Territory, was undertaken to determine if this species' climate response was dependent on elevation(Brookhouse and Bi, 2009). Samples were collected at 1350, 1475, and 1600 m asl and ring-width chronologies were developed that were compared to mean minimum and mean maximum temperatures as well as to precipitation.…”
mentioning
confidence: 99%